Entre o coercitivo e o educativo: análise da responsabilização socioeducativa no Programa de Medidas em Meio Aberto - SILVA, Regina Célia Nascimento (Universidade Federal do Pará, 2019)
The purpose of this study is to contextualize the application of socio - educational measures, the contradictions experienced by the institutions that attend adolescents who are responsible for infractions, and the pedagogical and sanctioning duty of the socio - education. It will be sought to understand the meanings and meanings that the adolescents accused of the practice of infractions attributing to the interventions directed to them, as well as the pedagogical practices developed in the Specialized Reference Center for Social Assistance (CREAS), the main municipal public institution , responsible for offering the service of monitoring socio-educational measures in the middle of the open, in the Municipality of Barcarena. The research methodology was based on a qualitative approach, based on bibliographical research and the application of questionnaires with the subjects of the research-adolescents in compliance with socio-educational measures in the Open Environment and pedagogues active in the socioeducation. As a theoretical reference, the research is supported by Michael Foucault's Birth of Biopolitics (2008) and Vigiar e Punir (1984), which emphasize the discourses, practices and devices of power and the different modes of government that mark the historical process of our emphasizing the concept of governance. The thinking presented by Loïc Wacquant in his books, Prisons of Misery (2001) and Punishing the Poor (2007), which, in general, portrays the consequences of a policy of exclusion adopted by the State, in order to isolate social interaction the less favored classes. It is based on the readings of Pinheiro (2006) and Rizzini (1997; 2009) as a way to understand how Brazilian legislation regarding children and adolescents has been historically constructed.